PENYALAHGUNAAN KEKUASAAN DALAM NOVEL ANIMAL FARM KARYA GEORGE ORWELL DAN NEGERI PARA BEDEBAH KARYA TERE LIYE: KAJIAN SASTRA BANDINGAN - Zilfa Achmad Bagtayan; Julianti Anamira Pobela; Siti Nurhalisa Pobela (Jurnal Pustaka Cendekia Pendidikan, 2025)
Abuse of power is a social phenomenon often reflected in literary works as a form of criticism of the reality of social life. This study aims to describe the similarities and differences in the forms of power in George Orwell's novel Animal Farm and Tere Liye's novel Negeri Para Bedebah. This study uses a comparative literature approach with Alan Swingewood's sociological analysis framework, which views literature as a social mirror and a means of understanding societal structures. The research method used is descriptive qualitative with content analysis techniques. The results of the study show significant similarities in both novels in terms of legal manipulation, the use of propaganda, and the exclusion of idealism for the sake of elite control. Fundamental differences are found in their sociological contexts: Animal Farm represents the protection of power in a totalitarian system based on physical revolution, while Negeri Para Bedebah reflects power in a modern capitalist system through economic manipulation and political networks. The conclusion of this study confirms that although written in different time and cultural settings, these two novels both threaten how uncontrolled power tends to become a tool of oppression that harms human values.